(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The Government of India spends a little over 1 per cent of Gross Domestic Product (GDP) on health, which is inadequate to provide better health care facilities to the people. It has been resulted that Indians spend major portions of health expenditure in the country from their personal resources. With the rise in health care costs due to emergence of private hospitals, expensive health technology and pharmaceuticals, there is need for adequate planning to protect sudden hospitalization. So, health insurance becomes imperative for everyone to look and be covered under a good health insurance policy. In order to health insurance industry has come up with innovative products due to increasing demand and facilitates access of comprehensive services to the people. This empirical and analytical research aimed to measure the growth of business performance in the health insurance market and also to identify the determinants of policyholders’ satisfaction level. The analysis reveals that there exists positive growth in different sectors’ health insurance services with respect to premium collection for the reference period 2009-10 to 2018-19. In addition, this study shows that more than 6/10th of the policy holders are highly satisfied with health insurance services. The factors namely coverage of illness, premium of the scheme, timely service, availability of web-based information and accessibility of branch offices are mainly determine to policyholders’ with lower and higher satisfaction towards health insurance services.